Effects caused by Covid-19 in the Ecuadorian productive network - Ramos, Josselyn (2021)
Given the emergence of Covid-19, Ecuador suffered a supply shock that prevented it from producing due to the sudden stoppage of productive activities. Additionally, international trade was partially interrupted, since imports and exports decreased, causing an external demand shock. As a result of the crisis, population uncertainty increased, generating a change in the behavior of agents, which translates into a reduction in spending on consumption of goods, services and capital. The spread of these effects in the economy results from a multiplicative behavior, attributed to the existence of productive chains and cascade effects that arise from the impact generated. Given the existence of interrelationships in the production network, the direct and indirect effects resulting from disturbances will be transmitted from one sector to another in different proportions, through input-output relationships, which allow determining their relative effect. These transmission mechanisms describe a circular trend, product of the interaction between the different economic sectors. In this context, it is relevant to analyze what is the incidence of the crisis caused by Covid-19 in the Ecuadorian economy, through the implementation of a Leontief model with foreign trade and gross added value, which will allow establishing the interrelationships of the activities productive activities and evaluate ex-ante economic shocks as a result of the pandemic.